PERAN KOMUNIKASI ANTARPRIBADI ORANGTUA DAN PENGASUH TERHADAPPERTUMBUHAN ANAK BALITA DITEMPAT PENITIPAN ANAK IRUKA JALAN JAMIN GINTING KM 8,5 MEDAN - Yerra Lolitha; Helen Vanhurk Sriwati Ningsih Sitorus (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
This study aims at analyzing factors making a child entrusted and the role of interpersonal communication between parents and babysitters on the growth of children under five. This study uses qualitative research methods with the subject of the leadership of the institution, caregivers, and parents in the Iruka children's nursery. Data collection uses the method of observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation and conclusion drawing. The results of this study indicate that the parent factor entrusts their children is due to busy parents who have to work to meet the economic needs of the household and teach children about new things that are educational and easy to socialize with other children; the role of interpersonal communication between parents and babysitters is the mutual openness and intimate interaction between parents and babysitters about the growth of children every day.